A pressure-resistant peripherally inserted central catheter is as useful as a central venous catheter for rapid fluid infusion: an in vitro study - Jun Maki; Makoto Sumie; Tomoko Ide; Masako Nagamatsu; Katsuyuki Matsushita; Kazuhiro Shirozu; Midoriko Higashi; Ken Yamaura (BMC Anesthesiology, 2022)
Abstract Background Although peripherally inserted central catheters (PICCs) have been widely used, they have not been frequently used in anesthesia practice. The central venous pressure measured via PICCs are reportedly as accurate as that measured via central venous catheters (CVCs), but the findings concerning rapid infusion are unclear. This study examined whether or not pressure-resistant PICCs could be used for rapid fluid infusion.  Methods The in-line pressure was measured in similar-sized double-lumen catheters—4-Fr PICC (55, 45 and 35 cm) and 17-G CVC (20 and 13 cm)—at flow rates of saline decided using a roller pump system. We also examined the flow rate at an in-line pressure of 300 mmHg, which is the critical pressure at which hemolysis is considered to occur during blood transfusion. Results The pressure-resistant PICCs obtained a high flow rate similar to that of CVCs, but the in-line pressures increased in proportion to the flow rate and catheter length. Flow rates at an intra-circuit pressure of 300 mmHg were not significantly different between the 45-cm PICC and 20-cm CVC. Conclusion Pressure-resistant PICCs can be used for rapid fluid infusion.